Availability of cookies during an academic course session affects evaluation of teaching. Issue 10 (29th June 2018) - Hessler, Michael; Pöpping, Daniel M; Hollstein, Hanna; Ohlenburg, Hendrik; Arnemann, Philip H; Massoth, Christina; Seidel, Laura M; Zarbock, Alexander; Wenk, Manuel
Abstract : Objectives: Results from end‐of‐course student evaluations of teaching (SETs) are taken seriously by faculties and form part of a decision base for the recruitment of academic staff, the distribution of funds and changes to curricula. However, there is some doubt as to whether these evaluation instruments accurately measure the quality of course content, teaching and knowledge transfer. We investigated whether the provision of chocolate cookies as a content‐unrelated intervention influences SET results. Methods: We performed a randomised controlled trial in the setting of a curricular emergency medicine course. Participants were 118 third‐year medical students. Participants were randomly allocated into 20 groups, 10 of which had free access to 500 g of chocolate cookies during an emergency medicine course session (cookie group) and 10 of which did not (control group). All groups were taught by the same teachers. Educational content and course material were the same for both groups. After the course, all students were asked to complete a 38‐question evaluation form. Results: A total of 112 students completed the evaluation form. The cookie group evaluated teachers significantly better than the control group (113.4 ± 4.9 versus 109.2 ± 7.3; p = 0.001, effect size 0.68). Course material was considered better (10.1 ± 2.3 versus 8.4 ± 2.8; p = 0.001, effect size 0.66) and summation scores evaluating the course overall were significantly higher (224.5 ± 12.5 versus 217.2 ± 16.1; p = 0.008, effect size 0.51) in the cookie group. Conclusions: The provision of chocolate cookies had a significant effect on course evaluation. These findings question the validity of SETs and their use in making widespread decisions within a faculty. Abstract : Hessler et al. question the validity of Student Evaluations of Teaching after demonstrating that provision of chocolate cookies had a significant effect on course evaluation.